“According to His Own Judgment”: The American Catholic Encounter with Organic Evolution, 1875–1896 - Mislin, David (Religion and American culture, 2012)
Between 1875 and 1896, the response of American Catholic thinkers to theories of organic evolution was characterized by little rancor and discord. Among the small number of clergy and lay intellectuals who addressed the subject, there existed a wide variety of positions on the scientific plausibility of such theories. These prominent Catholics were not deeply wedded to their views, however, and few saw any significant conflict between their religious commitments and biological evolution. This state of affairs stemmed from several elements of Catholic thought, particularly as it existed in the late-nineteenth-century United States: the conviction that church authority could mediate any apparent tension between science and Scripture; the affirmation that theories of organic evolution would not undermine existing theological tenets about the relationship between religion and science, as well as that between First Cause and secondary causes in nature; the belief that Catholic intellectuals since the time of Augustine had endorsed a system of natural development that closely resembled modern conceptions of evolution; and, most important, the insistence that the theory could be reconciled with the resurgent neo-Scholasticism that had come to dominate Catholic thought. Organic evolution proved far less significant in discussions of the relationship between religion and science among American Catholics than it did among Protestants, and it did little to contribute to the split of Catholics into liberal and conservative groups.